The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1074/jbc.m112.431957
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 Regulates Mutant SOD1 Aggregation through Two SMIR Motifs and Tubulin Acetylation

Abstract: Background:The role of HDAC6 in mutant SOD1 aggregation and ALS etiology is unclear. Results: HDAC6 interacted with mutant SOD1 via two SMIR motifs, and HDAC6 knockdown promoted aggregation of mutant SOD1. Conclusion: Mutant SOD1 can modulate HDAC6 activity and increase tubulin acetylation, which, in turn, facilitates mutant SOD1 aggregation. Significance: HDAC6 deficiency might be a converging point of various subtypes of ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 48 publications
2
55
0
Order By: Relevance
“…SIRT1 expression has been shown to be decreased in lungs of patients with COPD (54,55). Our data implicate SIRT1 as an HDAC6 deacetylase and suggest a model in which HDAC6 deacetylase activity is reduced by CS as a result of SIRT1 downregulation, resulting in acetylation and catalytic inhibition of HDAC6 (74). Interestingly, SIRT1 inhibition has been shown to enhance autophagy induced by CS in the lungs of Sirt1 +/-mice (75).…”
Section: Figure 10mentioning
confidence: 73%
“…SIRT1 expression has been shown to be decreased in lungs of patients with COPD (54,55). Our data implicate SIRT1 as an HDAC6 deacetylase and suggest a model in which HDAC6 deacetylase activity is reduced by CS as a result of SIRT1 downregulation, resulting in acetylation and catalytic inhibition of HDAC6 (74). Interestingly, SIRT1 inhibition has been shown to enhance autophagy induced by CS in the lungs of Sirt1 +/-mice (75).…”
Section: Figure 10mentioning
confidence: 73%
“…This phenotype was associated with an increase of α-tubulin acetylation and retrograde transport of mutated proteins. Mutant SOD1 oligomers and small aggregates sequester and inactivate HDAC6, favoring tubulin acetylation and leading to the formation of large pathologic inclusions [131]. Thus, if ELP3 represents a strong candidate to design new activator-based therapies, then much effort must be made to understand the precise outcomes of tubulin acetylation.…”
Section: Alsmentioning
confidence: 99%
“…These proteins are substrates of histone deacetylase (HDAC), which is likely to be dysfunctional in ALS patients. Concordantly, another study found that ALS-mutant SOD1 is capable of modulating HDAC6 activity (Gal et al, 2013), suggesting that the mutant protein may increase acetylation, potentially conferring proteasomal resistance and aiding the aggregation.…”
Section: Pathophysiologymentioning
confidence: 95%